Analisis pendapatan usaha tani bawang merah di Desa Waru Barat Kecamatan Waru Kabupaten Pamekasan - Nisak, Hoirun; Nugroho, Taufik Rizal Dwi Adi (Agriscience, 2024)
The agricultural sector is divided into 3 subsectors, namely food crops, plantations, and horticulture. One of the agricultural commodities in the horticulture subsector is shallots. Waru Barat village is one of the villages that produce shallot commodities in Pamekasan Regency. However, there are problems faced by farmers including harvesting activities simultaneously causing a decline in selling prices, farmers have not made records related to costs incurred and profits obtained, as well as the lack of availability of inorganic fertilizers. The purpose of this study is to: (1) analyze the income of shallot farmers in Waru Barat Village, (2) analyze the feasibility of shallot farming in Waru Barat Village. The methods used are revenue analysis and feasibility analysis. The Data used are primary data obtained from interviews directly with farmers using questionnaires. The results showed that the average income of shallot farmers amounted to Rp146,971,031/Ha in 2 planting seasons. The results of the feasibility analysis of shallot farming are feasible to be developed because the value of R/C ratio is 3.26 1 and the value of B/C ratio is 2.26 1. Farmers can use seeds, fertilizers as needed and take care of the means of production for a longer service life.